Location-based Mobile Learning Applications: A conceptual framework for co-design - Lliteras, Alejandra Beatriz (2017)
This paper presents a conceptual framework for codesign (by multidisciplinary team) Location-based Mobile Learning Applications. Four stages are identified related with this kind of applications: conceptual design, development cycle, put into practice and evaluation. This paper is focus on the first stage, the conceptual design. For this stage, relevant features are described. In particular, good practices of software engineering could be used for the design stage. As part of conceptual design, guidelines are provided to define learning content decoupled of relevant locations of physical space (indoor or outdoor). This allows to reuse both in different applications.